2019
DOI: 10.3389/fpls.2019.00994
|View full text |Cite
|
Sign up to set email alerts
|

MdGGT1 Impacts Apple miR156 Precursor Levels via Ontogenetic Changes in Subcellular Glutathione Homeostasis

Abstract: The vegetative phase change in flowering plants is controlled by microRNA156 (miR156) under transcriptional regulation. However, the developmental signals upstream of miR156 are not well understood. The glutathione/glutathione disulfide (GSH/GSSG) ratios and GSH levels decline significantly during phase change, which is consistent with miR156 expression in apple ( Malus domestica Borkh.). Here, we found that the content of protein conjugated glutathione was remarkably higher in chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(116 reference statements)
2
8
0
Order By: Relevance
“…This indicated that the NTRC/2-Cys Prx level was robustly maintained during the phase change (Figure 3). In this study, both GSH content and the GSH/GSSG ratio decreased significantly during ontogenesis, which supported our previous hypothesis that a shift in major antioxidants from GSH to ASC during the phase change attenuated the cellular ROS scavenging ability [11,18,22]. This was consistent with that GSH plays a key role in ASC-GSH coupled non-enzyme ROS scavenging in plant cells [59].…”
Section: The Accumulation Of Chloroplastic H 2 O 2 In the Adult Phase Is Due To Decreased Scavenging Capacity Rather Than Higher Photosynsupporting
confidence: 91%
See 2 more Smart Citations
“…This indicated that the NTRC/2-Cys Prx level was robustly maintained during the phase change (Figure 3). In this study, both GSH content and the GSH/GSSG ratio decreased significantly during ontogenesis, which supported our previous hypothesis that a shift in major antioxidants from GSH to ASC during the phase change attenuated the cellular ROS scavenging ability [11,18,22]. This was consistent with that GSH plays a key role in ASC-GSH coupled non-enzyme ROS scavenging in plant cells [59].…”
Section: The Accumulation Of Chloroplastic H 2 O 2 In the Adult Phase Is Due To Decreased Scavenging Capacity Rather Than Higher Photosynsupporting
confidence: 91%
“…We examined whether tetrapyrrole-PNRS was affected by the GSH status by using GL-3 transgenic lines over-expressing gamma-glutamyl transferase gene1 (OEMdGGT1) and MdGGT1-RNAi lines. It is reported that GSH levels and miR156 expression are elevated in OEMdGGT1 and decreased in MdGGT1-RNAi lines [22]. We found that Mg-Proto IX and heme levels were relatively lower in OEMdGGT1 lines but were significantly higher in MdGGT1-RNAi lines compared with WT (Figure 9A,B).…”
Section: Validation Of the Relationship Between Tetrapyrroles And Mir156 Expression Or Gsh Contentsupporting
confidence: 50%
See 1 more Smart Citation
“…The importance of ROS scavenging is underpinned by the similar phenotype of Arabidopsis pex10 mutants impaired in peroxisome biogenesis [154] and a more permissive delayed embryogenesis phenotype in str1 str2 mutants impaired in RBOH-associated mitochondrial proteins [155]. Provided that ROS can serve as signaling molecules [156,157], it is possible that ROS formation, scavenging, and signal transduction may represent the prominent players in novel embryonic timing control mechanisms as well.…”
Section: Two-membrane Organelle Functioning and Energy Metabolismmentioning
confidence: 99%
“…11 Moreover, abnormally high expression level of GGT could lead to the breakdown of redox homeostasis in intracellular environment and eventually result in cancerization. 5,12 GGT can promotes the growth and proliferation of tumor cells by mediating the circulation of g-Glu in tumor cells. 13 It also can promotes cancer metastasis and drug resistance of tumors.…”
Section: Introductionmentioning
confidence: 99%